Improving Environmental Sustainability in Road Projects - Montgomery, Robert (World Bank, Washington, DC, 2015)
The focus of this document is to provide a wide range of ideas and options to improve the inclusion of environmental sustainability throughout the road transportation project cycle (system planning, project planning and design, construction, and operation and maintenance) based on environmental sustainability indicators and highlighting environmentally sustainable products and materials for road construction. Sustainable economic growth in low- and middle-income countries is a key to poverty reduction and shared prosperity, which in part is dependent on reliable and safe transportation systems. Road and highway systems provide a critical function in creating and maintaining a desirable quality of life.